Hard alloy composite coating and preparation method thereof

Through multi-layer structural design and nano yttrium dioxide particles doping, the interfacial stress concentration problem caused by the difference in expansion coefficient in cemented carbide composite coating is solved, the interface bond strength and wear resistance of the coating are improved, and the coating life is extended.

CN120400839APending Publication Date: 2025-08-01GANSU LINTAO SURFACE TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510623623.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-15
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The expansion coefficients of the high-hard wear-resistant layer and the high-temperature oxidation-resistant layer in the existing cemented carbide composite coating system are significant, resulting in concentrated interface stress and thermal cyclic load during high-speed cutting lead to coating layering.

Method used

A multi-layer structural design is adopted, including a matrix layer, a transition layer, a gradient functional layer, a composite layer and a surface layer. It is formed by plasma-enhanced chemical vapor deposition, multi-source chemical vapor deposition and high-power pulsed magnetron sputtering and other technologies. A continuous thermal expansion coefficient transition zone is formed in the gradient functional layer, and an Al-Ti-O eutectic phase is generated at the interface between the gradient functional layer and the composite layer, combining the doping of nano yttrium trioxide particles.

Benefits of technology

It significantly improves the interface bonding strength and layering resistance of cemented carbide composite coating, reduces wear rate, and extends the life of the coating under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120400839A_ABST
    Figure CN120400839A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of hard alloy, in particular to a hard alloy composite coating and a preparation method thereof.The hard alloy composite coating comprises the following layer structures deposited in sequence: a matrix layer, hard alloy composed of, by mass, 8-10% of cobalt, 0.3-0.8% of chromium carbide and the balance tungsten carbide, a transition layer and a titanium nitride layer; plasma enhanced chemical vapor deposition equipment is adopted to deposit on the surface of the base body layer at 870-890 DEG C under the pressure of 200 MPa to form the gradient functional layer and the titanium carbonitride layer, and the carbon-nitrogen atom ratio of the gradient functional layer and the titanium carbonitride layer is changed from 1.2: 1 of the inner layer to 0.6: 1 of the outer layer in a gradient mode. According to the preparation method, through the design of the gradient functional layer, a continuous thermal expansion coefficient transition area is formed in the titanium carbonitride layer, so that the interface thermal stress and the interface crack density are greatly reduced, and the interface bonding strength of the hard alloy composite coating can be remarkably improved; and the layering resistance of the coating in high-speed cutting can be remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cemented carbides, and particularly to a cemented carbide composite coating and a preparation method thereof. Background Art

[0002] The cemented carbide composite coating is a multi-functional thin film formed on the surface of a cemented carbide material with tungsten carbide as the matrix and cobalt as the binder phase through a chemical vapor deposition technique, and is widely used in extreme working condition fields such as high-speed cutting tools and hot-end components of aeroengines.

[0003] The existing cemented carbide composite coating system is usually composed of a combination of a high-hardness wear-resistant layer and a high-temperature oxidation-resistant layer. However, there is a significant problem of a large difference in the coefficient of thermal expansion between the high-hardness wear-resistant layer and the high-temperature oxidation-resistant layer in the coating system, which leads to interfacial stress concentration and the problem of coating delamination caused by thermal cycling loads during high-speed cutting.

[0004] Based on this, the present invention provides a cemented carbide composite coating and a preparation method thereof. Summary of the Invention

[0005] The purpose of the present invention is to provide a cemented carbide composite coating and a preparation method thereof to solve the problems raised in the above background art.

[0006] To achieve the above purpose, the present invention provides the following technical solution: A cemented carbide composite coating includes the following layer structures deposited in sequence:

[0007] Substrate layer: A cemented carbide composed of 8-10% cobalt by mass, 0.3-0.8% chromium carbide, and the balance being tungsten carbide;

[0008] Intermediate layer: A titanium nitride layer deposited on the surface of the substrate layer by a plasma-enhanced chemical vapor deposition apparatus at 870-890 °C and a pressure of 200 MPa;

[0009] Gradient functional layer: A titanium carbonitride layer with a carbon-to-nitrogen atomic ratio varying from 1.2:1 in the inner layer to 0.6:1 in the outer layer;

[0010] Composite layer: An alumina layer in which the proportion of α-alumina is 50-70%, and the balance is titanium carbonitrogen oxide, and the atomic ratio of titanium, carbon, oxygen, and nitrogen in the titanium carbonitrogen oxide is 1:0.6:0.2:0.2;

[0011] Surface layer: A nanocrystalline titanium nitride layer with a grain size ≤ 50 nm, deposited by a high-power pulsed magnetron sputtering apparatus at a bias voltage of -100 V to -150 V and a power density of 3-5 W / cm 2 conditions.

[0012] Preferably, the thickness of the intermediate layer is 0.2-0.5 μm, and the thickness of the gradient functional layer is 4-8 μm.

[0013] Preferably, the thickness of the composite layer is 1-2 μm, and the thickness of the surface layer is 0.5-1 μm.

[0014] Preferably, the composite layer is doped with yttrium trioxide nanoparticles with a mass ratio of 0.5-1.2% of the total mass of the composite layer, and the particle size is 20-50 nm. The nanoparticles are synchronously injected during the deposition process by an ultrasonic atomization doping device, with an atomization frequency of 20-40 kHz and a carrier gas flow rate of 5-10 L / min.

[0015] Preferably, a method for preparing a cemented carbide composite coating includes the following steps:

[0016] Step 1: Substrate pretreatment. The surface of the substrate is treated with a sandblaster, and the abrasive particle size is set to 80-120 mesh, and the compressed air pressure is 0.5-0.8 MPa. Then the substrate is transferred to an ultrasonic cleaner and cleaned in a sodium hydroxide solution with a pH value of 10 for 30 min. Then it is transferred to a radio frequency plasma activation device, with a set power of 300 W and an argon gas flow rate of 50 mL / min, and activated under a vacuum of 1×10 -2 Pa for 20 minutes;

[0017] Step 2: Deposition of the transition layer. Plasma enhanced chemical vapor deposition is used. Titanium tetrachloride is vaporized and mixed with high-purity nitrogen and hydrogen in a volume ratio of 1:2:4 to form a mixed gas. After the mixed gas enters the deposition chamber, a 10-15 MHz radio frequency power supply is applied to generate plasma. The substrate temperature is maintained at 870-890 °C, and a -100 V bias voltage is applied to promote the directional deposition of ions, and a deposition transition layer is formed on the surface of the substrate.

[0018] Step 3: Deposition of the gradient functional layer. Through an MT-CVD device equipped with dual-temperature control, the temperature of the main heating zone is set to 850-900 °C, and the temperature of the secondary heating zone is set to 750-800 °C. Using an organic nitrogen-carbon compound as the carbon source and nitrogen source, activated carbon and nitrogen groups are generated by decomposition at high temperature. At the same time, a carrier gas is introduced to carry the titanium source compound, and the deposition process is carried out under the condition of 50-60 MPa to form a gradient functional layer deposited on the surface of the deposition transition layer.

[0019] Step 4: Deposition of the composite layer. A multi-source chemical vapor deposition device is used, and the deposition of the composite layer is achieved by alternately controlling two gas paths. The first gas path is a mixed gas of aluminum trichloride, carbon dioxide, and water vapor, and the volume ratio of aluminum trichloride, carbon dioxide, and water vapor is 1:3:0.05. The second gas path is a mixed gas of titanium tetrachloride and nitrogen, and the volume ratio of titanium tetrachloride and nitrogen is 1:2. A composite layer is formed on the surface of the gradient functional layer.

[0020] Step 5: Surface layer deposition: Use a high-power pulsed magnetron sputtering device with a titanium target purity of ≥99.99%, a target-substrate distance of 80 mm, a pulse frequency of 1000 Hz, and a duty cycle of 50%.

[0021] Preferably, the preparation method of the cemented carbide composite coating includes the following further treatment steps:

[0022] Step 1: Bonding of the substrate layer and the transition layer: Under argon protection, place the substrate layer and the titanium nitride transition layer in a vacuum annealing furnace, heat up to 800 - 850 °C at a rate of 15 °C / min, and hold for 30 min;

[0023] Step 2: Bonding of the transition layer and the gradient functional layer. Use an ion implantation device to implant carbon ions with an energy of 40 - 50 keV onto the surface of the transition layer, with a beam current density of 60 μA / cm 2 and a dose of 1×10 17 ions / cm 2 to form a nanoscale carbon-enriched transition zone;

[0024] Step 3: Bonding of the gradient functional layer and the composite layer. Use a laser remelting device to scan the surface of the gradient functional layer at a wavelength of 1064 nm and a power density of 1×10 4 W / cm 2 so that the surface layer area of the gradient functional layer melts and forms an Al-Ti-O eutectic phase with the alumina layer;

[0025] Step 4: Bonding of the composite layer and the surface layer. Before magnetron sputtering deposition of nano titanium nitride, bombard the surface of the composite layer with argon plasma, set the power density at 0.5 W / cm2 for 10 min to form a rough interface and activate the surface, and then perform nano titanium nitride deposition to fill the interface microstructure with titanium oxide and generate a roughened interface of 5 - 10 nm on the surface of the composite layer, which is the surface layer;

[0026] Step 5: Overall densification treatment. Place the coating in a hot isostatic pressing device, set the temperature at 800 - 900 °C, and hold for 1 hour under an argon pressure of 200 MPa so that the porosity of each layer is ≤0.5% and the thickness of the interface diffusion zone is ≥0.2 μm.

[0027] Preferably, for the sandblasting machine in Step 1, set the impeller rotation speed at 2600 - 2800 r / min and the abrasive delivery rate at 2 - 3 kg / min.

[0028] Preferably, in Step 3, simultaneously turn on the ion implantation device to implant nitrogen ions with an energy of 100 keV, a beam current density of 80 μA / cm 2 and an implantation dose of 3×10 17 ions / cm 2 at an implantation angle of 15° - 30°.

[0029] Preferably, the step 4 is interrupted for 5-10 minutes after each 0.5 μm of deposition.

[0030] Preferably, in the preparation method of the cemented carbide composite coating, the sputtering chamber of the magnetron sputtering equipment in step 5 is equipped with a quadrupole mass spectrometer to monitor the oxygen partial pressure in real time ≤1×10 -3 Pa, nitrogen partial pressure is controlled at 0.3-0.5Pa.

[0031] Compared with the prior art, the present invention has the following beneficial effects:

[0032] 1. In this preparation method, a continuous thermal expansion coefficient transition zone is formed in the titanium carbonitride layer through the design of a gradient functional layer, which greatly reduces the interface thermal stress and interface crack density, and significantly improves the interface bonding strength of the cemented carbide composite coating. By alleviating the interlayer thermal mismatch design, the coating's anti-delamination ability in high-speed cutting can be significantly improved.

[0033] 2. In this preparation method, after laser remelting treatment during the preparation of the cemented carbide composite coating, an Al-Ti-O eutectic phase is generated at the interface between the gradient functional layer and the composite layer. Combined with the pinning effect of nano-yttrium trioxide on the grain boundaries, the wear rate can be greatly reduced, which makes up for the technical defect of commercially available coatings that have a high wear rate due to the lack of eutectic strengthening. The synergistic effect of laser remelting and nano-doping significantly improves the wear resistance of the cemented carbide composite coating.

[0034] 3. In this preparation method, after the composite layer of the coating is doped with nano-yttrium oxide particles, the alumina grain boundaries are pinned, and the oxygen diffusion coefficient and oxidation increment can be significantly reduced. Therefore, yttrium oxide can significantly extend the life of the coating under high temperature conditions of 1000°C through grain boundary pinning and diffusion blocking. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is an overall diagram of a cemented carbide composite coating of the present invention;

[0036] Figure 2 This is a layer structure diagram of a cemented carbide composite coating of the present invention. DETAILED DESCRIPTION

[0037] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0038] Example 1:

[0039] This embodiment provides a cemented carbide composite coating, including the following layer structures deposited in sequence:

[0040] Substrate layer: Cemented carbide composed of 8% cobalt, 0.3% chromium carbide, and the balance being tungsten carbide by mass;

[0041] Transition layer: Titanium nitride layer, deposited on the surface of the substrate layer by a plasma-enhanced chemical vapor deposition apparatus at 870 °C and a pressure of 200 MPa;

[0042] Gradient functional layer: Titanium carbonitride layer, with the carbon-to-nitrogen atomic ratio varying from 1.2:1 in the inner layer to 0.6:1 in the outer layer;

[0043] Composite layer: Alumina layer, where α-alumina accounts for 50% by mass, and the balance is titanium carbonitrogen oxide, and the atomic ratio of titanium, carbon, oxygen, and nitrogen in the titanium carbonitrogen oxide is 1:0.6:0.2:0.2;

[0044] Surface layer: Nanocrystalline titanium nitride layer, with a grain size ≤ 50 nm, deposited by a high-power pulsed magnetron sputtering apparatus under a bias voltage of -100 V and a power density of 3 W / cm 2 conditions.

[0045] Among them, the thickness of the transition layer is 0.2 μm, and the thickness of the gradient functional layer is 4 μm.

[0046] Among them, the thickness of the composite layer is 1 μm, and the thickness of the surface layer is 0.5 μm.

[0047] Among them, the composite layer is doped with nano-yttrium trioxide particles accounting for 0.5% of the total mass of the composite layer, with a particle size of 20 nm, and is synchronously injected during the deposition process by an ultrasonic atomization doping apparatus, with an atomization frequency of 20 kHz and a carrier gas flow rate of 5 L / min.

[0048] Among them, a method for preparing a cemented carbide composite coating includes the following steps:

[0049] Step 1: Substrate pretreatment. The surface of the substrate is treated with a sandblaster, with the abrasive particle size set at 80 mesh and the compressed air pressure at 0.5 MPa. Then the substrate is transferred to an ultrasonic cleaning machine and cleaned in a sodium hydroxide solution with a pH value of 10 for 30 min. Then it is transferred to a radio frequency plasma activation apparatus, with the power set at 300 W, the argon gas flow rate at 50 mL / min, and the vacuum degree at 1×10 -2 Pa for 20 minutes for activation;

[0050] Step 2: Deposit the transition layer. Using plasma-enhanced chemical vapor deposition, vaporize titanium tetrachloride and mix it with high-purity nitrogen and hydrogen in a volume ratio of 1:2:4 to form a mixed gas. After the mixed gas enters the deposition chamber, apply a 10 MHz radio frequency power supply to generate plasma. Keep the substrate temperature at 870 °C and apply a -100 V bias voltage to promote the directional deposition of ions and form a deposition transition layer on the substrate surface;

[0051] Step 3: Deposit the gradient functional layer. Through an MT-CVD device equipped with dual-temperature control, set the temperature of the main heating zone at 850 °C and the temperature of the secondary heating zone at 750 °C. Use an organic nitrogen-carbon compound as the carbon source and nitrogen source, which decomposes at high temperature to generate activated carbon and nitrogen groups. At the same time, introduce a carrier gas to carry the titanium source compound. The deposition process is carried out under a condition of 50 MPa to form a gradient functional layer deposited on the surface of the deposition transition layer;

[0052] Step 4: Deposit the composite layer. Use a multi-source chemical vapor deposition device to achieve the deposition of the composite layer through the alternating control of dual gas paths. The first gas path is a mixed gas of aluminum trichloride, carbon dioxide, and water vapor, and the volume ratio of aluminum trichloride, carbon dioxide, and water vapor is 1:3:0.05. The second gas path is a mixed gas of titanium tetrachloride and nitrogen, and the volume ratio of titanium tetrachloride and nitrogen is 1:2. A composite layer is formed on the surface of the gradient functional layer;

[0053] Step 5: Surface layer deposition: Use a high-power pulsed magnetron sputtering device with a titanium target purity of ≥99.99%, a target-substrate distance of 80 mm, a pulse frequency of 1000 Hz, and a duty cycle of 50%.

[0054] Among them, the preparation method of the cemented carbide composite coating includes the following further treatment steps:

[0055] Step 1: Bonding of the substrate layer and the transition layer: Under argon protection, place the substrate layer and the titanium nitride transition layer in a vacuum annealing furnace, heat it to 800 °C at a rate of 15 °C / min, and hold for 30 min;

[0056] Step 2: Bonding of the transition layer and the gradient functional layer. Use an ion implantation device to inject carbon ions with an energy of 40 keV onto the surface of the transition layer, with a beam current density of 60 μA / cm 2 , and a dose of 1×10 17 ions / cm 2 to form a nanoscale carbon-rich transition zone;

[0057] Step 3: Bonding of the gradient functional layer and the composite layer. Use a laser remelting device to scan the surface of the gradient functional layer under the conditions of a wavelength of 1064 nm and a power density of 1×10 4 W / cm 2 so that the surface layer area of the gradient functional layer melts and forms an Al-Ti-O eutectic phase with the alumina layer;

[0058] Step 4: Bond the composite layer with the surface layer. Before magnetron sputtering deposition of nano-titanium nitride, bombard the surface of the composite layer with argon plasma, set the power density at 0.5 W / cm² and the time at 10 min to form a rough interface and activate the surface, and then deposit nano-titanium nitride to fill the interface microstructure with titanium oxide, generating a roughened interface of 5 nm on the surface of the composite layer, which is the surface layer;

[0059] Step 5: Overall densification treatment. Place the coating in a hot isostatic pressing device, set the temperature at 800 °C, hold the pressure for 1 hour under an argon pressure of 200 MPa to make the porosity of each layer ≤ 0.5% and the thickness of the interface diffusion zone ≥ 0.2 μm.

[0060] Among them, in Step 1, for the sandblasting machine, set the impeller rotation speed at 2600 r / min and the abrasive delivery rate at 2 kg / min.

[0061] Among them, in Step 3, simultaneously turn on the ion implantation device, implant nitrogen ions with an implantation energy of 100 keV and a beam current density of 80 μA / cm 2 and an implantation dose of 3×10 17 ions / cm 2 at an implantation angle of 15°.

[0062] Among them, in Step 4, interrupt for 5 min after depositing every 0.5 μm.

[0063] Among them, for the preparation method of the cemented carbide composite coating, in Step 5, the sputtering chamber of the magnetron sputtering device is equipped with a quadrupole mass spectrometer to continuously monitor that the oxygen partial pressure ≤ 1×10 -3 Pa and the nitrogen partial pressure is controlled at 0.3 Pa.

[0064] Example 2. A cemented carbide composite coating includes the following layer structures deposited in sequence:

[0065] Substrate layer: Cemented carbide composed of 10% cobalt, 0.8% chromium carbide, and the balance tungsten carbide by mass;

[0066] Transition layer: Titanium nitride layer, deposited on the surface of the substrate layer by a plasma enhanced chemical vapor deposition device at 890 °C and a pressure of 200 MPa;

[0067] Gradient functional layer: Titanium carbonitride layer, with the carbon to nitrogen atomic ratio varying from 1.2:1 in the inner layer to 0.6:1 in the outer layer;

[0068] Composite layer: Aluminum oxide layer, in which the proportion of α-aluminum oxide is 70%, and the balance is carbonitrogen titanium oxide, and the atomic ratio of titanium, carbon, oxygen, and nitrogen in the carbonitrogen titanium oxide is 1:0.6:0.2:0.2;

[0069] Surface layer: nanocrystalline titanium nitride layer with grain size ≤ 50 nm, deposited by a high-power pulsed magnetron sputtering device under a bias voltage of -150 V and a power density of 5 W / cm 2 condition.

[0070] Among them, the thickness of the transition layer is 0.5 μm, and the thickness of the gradient functional layer is 8 μm.

[0071] Among them, the thickness of the composite layer is 2 μm, and the thickness of the surface layer is 1 μm.

[0072] Among them, the composite layer is doped with yttrium trioxide nanoparticles with a total mass ratio of 1.2% in the composite layer, the particle size is 50 nm, and they are synchronously injected during the deposition process by an ultrasonic atomization doping device, the atomization frequency is 40 kHz, and the carrier gas flow rate is 10 L / min.

[0073] Among them, a preparation method of a cemented carbide composite coating includes the following steps:

[0074] Step 1: Substrate pretreatment. The surface of the substrate is treated by a sandblasting machine, the abrasive particle size is set to 120 mesh, the compressed air pressure is 0.8 MPa, and then the substrate is transferred to an ultrasonic cleaning machine and cleaned in a sodium hydroxide solution with a pH value of 10 for 30 min, and then transferred to a radio frequency plasma activation device, the power is set to 300 W, the argon gas flow rate is 50 mL / min, and it is activated under a vacuum of 1×10 -2 Pa for 20 minutes;

[0075] Step 2: Deposit the transition layer. By plasma enhanced chemical vapor deposition, titanium tetrachloride is vaporized and mixed with high-purity nitrogen and hydrogen in a volume ratio of 1:2:4 to form a mixed gas. After the mixed gas enters the deposition chamber, a 15 MHz radio frequency power supply is applied to generate plasma, the substrate temperature is maintained at 890 °C, and a -100 V bias voltage is applied to promote the directional deposition of ions, and then a deposition transition layer is formed on the substrate surface;

[0076] Step 3: Deposit the gradient functional layer. Through an MT-CVD device equipped with dual-temperature control, the temperature of the main heating zone is set to 900 °C, and the temperature of the secondary heating zone is set to 800 °C. Using an organic nitrogen-carbon compound as a carbon source and a nitrogen source, activated carbon and nitrogen groups are decomposed at high temperature. At the same time, a carrier gas is introduced to carry the titanium source compound, and the deposition process is carried out under a condition of 60 MPa to form a gradient functional layer deposited on the surface of the deposition transition layer;

[0077] Step 4: Deposit the composite layer. Using a multi-source chemical vapor deposition device, the deposition of the composite layer is achieved through the alternating control of two gas paths. The first gas path is a mixed gas of aluminum trichloride, carbon dioxide, and water vapor, and the volume ratio of aluminum trichloride, carbon dioxide, and water vapor is 1:3:0.05. The second gas path is a mixed gas of titanium tetrachloride and nitrogen, and the volume ratio of titanium tetrachloride and nitrogen is 1:2. A composite layer is formed on the surface of the gradient functional layer;

[0078] Step 5: Surface layer deposition: Use a high-power pulsed magnetron sputtering device with a titanium target purity of ≥99.99%, a target-substrate distance of 80 mm, a pulse frequency of 1000 Hz, and a duty cycle of 50%.

[0079] Among them, the preparation method of the cemented carbide composite coating includes the following further treatment steps:

[0080] Step 1: Bonding of the substrate layer and the transition layer: Under argon protection, place the substrate layer and the titanium nitride transition layer in a vacuum annealing furnace, heat it to 850 °C at a rate of 15 °C / min, and hold for 30 min;

[0081] Step 2: Bonding of the transition layer and the gradient functional layer. Use an ion implantation device to implant carbon ions with an energy of 50 keV into the surface of the transition layer, with a beam current density of 60 μA / cm 2 and a dose of 1×10 17 ions / cm 2 to form a nanoscale carbon-enriched transition zone;

[0082] Step 3: Bonding of the gradient functional layer and the composite layer. Use a laser remelting device to scan the surface of the gradient functional layer at a wavelength of 1064 nm and a power density of 1×10 4 W / cm 2 so that the surface layer area of the gradient functional layer melts and forms an Al-Ti-O eutectic phase with the alumina layer;

[0083] Step 4: Bonding of the composite layer and the surface layer. Before magnetron sputtering deposition of nano-titanium nitride, use argon plasma to bombard the surface of the composite layer, set the power density to 0.5 W / cm2 and the time to 10 min to form a rough interface and activate the surface, and then carry out nano-titanium nitride deposition to fill the interface microstructure with titanium oxide and generate a 10-nm roughened interface on the surface of the composite layer, which is the surface layer;

[0084] Step 5: Overall densification treatment. Place the coating in a hot isostatic pressing device, set the temperature to 900 °C, and hold for 1 hour under an argon pressure of 200 MPa to make the porosity of each layer ≤0.5% and the thickness of the interface diffusion zone ≥0.2 μm.

[0085] Among them, in Step 1, for the sandblasting machine, set the impeller speed to 2800 r / min and the abrasive conveying rate to 3 kg / min.

[0086] Among them, in Step 3, simultaneously turn on the ion implantation device and implant nitrogen ions with an energy of 100 keV, with a beam current density of 80 μA / cm 2 and an implantation dose of 3×10 17 ions / cm 2 at an implantation angle of 30°.

[0087] Among them, in step four, after depositing 0.5 μm each time, it is interrupted for 10 min.

[0088] Among them, for the preparation method of the cemented carbide composite coating, in step five, the sputtering chamber of the magnetron sputtering equipment is equipped with a quadrupole mass spectrometer to monitor the oxygen partial pressure ≤ 1×10 -3 Pa in real time, and the nitrogen partial pressure is controlled at 0.5 Pa.

[0089] Example 3, a cemented carbide composite coating, including the following layer structures deposited in sequence:

[0090] Substrate layer: Cemented carbide composed of 9% cobalt, 0.5% chromium carbide, and the balance being tungsten carbide by mass;

[0091] Transition layer: Titanium nitride layer, deposited on the surface of the substrate layer by a plasma enhanced chemical vapor deposition equipment at 880 °C and a pressure of 200 MPa;

[0092] Gradient functional layer: Titanium carbonitride layer, with the carbon-nitrogen atomic ratio varying from 1.2:1 in the inner layer to 0.6:1 in the outer layer;

[0093] Composite layer: Aluminum oxide layer, in which the proportion of α-aluminum oxide is 60%, and the balance is carbonitrogen titanium oxide. The atomic ratio of titanium, carbon, oxygen, and nitrogen in the carbonitrogen titanium oxide is 1:0.6:0.2:0.2;

[0094] Surface layer: Nanocrystalline titanium nitride layer, with a grain size ≤ 50 nm, deposited by a high power pulsed magnetron sputtering equipment under a bias voltage of -125 V and a power density of 4 W / cm 2 conditions.

[0095] Among them, the thickness of the transition layer is 0.3 μm, and the thickness of the gradient functional layer is 6 μm.

[0096] Among them, the thickness of the composite layer is 1.5 μm, and the thickness of the surface layer is 0.8 μm.

[0097] Among them, the composite layer is doped with nano-yttrium trioxide particles accounting for 0.9% of the total mass of the composite layer. The particle size is 35 nm, and it is synchronously injected during the deposition process by an ultrasonic atomization doping equipment. The atomization frequency is 30 kHz, and the carrier gas flow rate is 8 L / min.

[0098] Among them, a preparation method of a cemented carbide composite coating includes the following steps:

[0099] Step 1: Substrate pretreatment. The surface of the substrate is treated with a sandblaster, setting the abrasive particle size to 100 mesh and the compressed air pressure to 0.7 MPa. Then the substrate is transferred to an ultrasonic cleaner and cleaned in a sodium hydroxide solution with a pH value of 10 for 30 minutes. After that, it is transferred to a radio frequency plasma activation device, setting the power to 300 W and the argon gas flow rate to 50 mL / min, and activating it for 20 minutes under the condition of a vacuum degree of 1×10 -2 Pa;

[0100] Step 2: Depositing the transition layer. Using plasma enhanced chemical vapor deposition, titanium tetrachloride is vaporized and mixed with high-purity nitrogen and hydrogen in a volume ratio of 1:2:4 to form a mixed gas. After the mixed gas enters the deposition chamber, a 12 MHz radio frequency power supply is applied to generate plasma. Keeping the substrate temperature at 880 °C and applying a -100 V bias voltage to promote the directional deposition of ions, a deposition transition layer is formed on the surface of the substrate;

[0101] Step 3: Depositing the gradient functional layer. Through an MT-CVD device equipped with dual-temperature control, setting the temperature of the main heating zone to 880 °C and the temperature of the secondary heating zone to 780 °C, using an organic nitrogen-carbon compound as the carbon source and nitrogen source, decomposing it at high temperature to generate activated carbon and nitrogen groups, and simultaneously introducing a carrier gas to carry the titanium source compound. The deposition process is carried out under the condition of 55 MPa, and a gradient functional layer is formed on the surface of the deposition transition layer;

[0102] Step 4: Depositing the composite layer. Using a multi-source chemical vapor deposition device, the composite layer deposition is achieved through the alternating control of dual gas paths. The first gas path is a mixed gas of aluminum trichloride, carbon dioxide, and water vapor, and the volume ratio of aluminum trichloride, carbon dioxide, and water vapor is 1:3:0.05. The second gas path is a mixed gas of titanium tetrachloride and nitrogen, and the volume ratio of titanium tetrachloride and nitrogen is 1:2. A composite layer is formed on the surface of the gradient functional layer;

[0103] Step 5: Surface layer deposition: Using a high-power pulsed magnetron sputtering device, the purity of the titanium target is ≥99.99%, the target-substrate distance is 80 mm, the pulse frequency is 1000 Hz, and the duty cycle is 50%.

[0104] Among them, the preparation method of the cemented carbide composite coating includes the following further treatment steps:

[0105] Step 1: Bonding between the substrate layer and the transition layer. Under the protection of argon gas, the substrate layer and the titanium nitride transition layer are placed in a vacuum annealing furnace, heated to 830 °C at a rate of 15 °C / min, and held for 30 minutes;

[0106] Step 2: Bonding between the transition layer and the gradient functional layer. Using an ion implantation device to inject carbon ions with an energy of 45 keV into the surface of the transition layer, the beam current density is 60 μA / cm 2 2, and the dose is 1×10 17 ions / cm 2, a nanoscale carbon-rich transition zone is formed;

[0107] Step 3: The gradient functional layer is combined with the composite layer. Using a laser remelting device, scan the surface of the gradient functional layer at a wavelength of 1064 nm and a power density of 1×10 4 W / cm 2 conditions, so that the surface layer area of the gradient functional layer melts and forms an Al-Ti-O eutectic phase with the alumina layer;

[0108] Step 4: The composite layer is combined with the surface layer. Before magnetron sputtering to deposit nano titanium nitride, the surface of the composite layer is bombarded with argon plasma, the power density is set to 0.5 W / cm2, and the time is 10 min to form a rough interface and activate the surface. Then, nano titanium nitride is deposited to fill the interface microstructure with titanium oxide, and a roughened interface of 8 nm is generated on the surface of the composite layer, which is the surface layer;

[0109] Step 5: Overall densification treatment. Place the coating in a hot isostatic pressing device, set the temperature to 880 °C, and hold the pressure for 1 hour under an argon pressure of 200 MPa, so that the porosity of each layer is ≤0.5%, and the thickness of the interface diffusion zone is ≥0.2 μm.

[0110] Among them, in Step 1, for the sandblasting machine, the impeller rotation speed is set to 2700 r / min, and the abrasive conveying rate is 2.5 kg / min.

[0111] Among them, in Step 3, the ion implantation device is turned on synchronously, nitrogen ions with an implantation energy of 100 keV are implanted, and the beam current density is 80 μA / cm 2 and the implantation dose is 3×10 17 ions / cm 2 , and the implantation angle is 25°.

[0112] Among them, in Step 4, after depositing 0.5 μm each time, it is interrupted for 5 - 10 min.

[0113] Among them, for the preparation method of the cemented carbide composite coating, in Step 5, the sputtering chamber of the magnetron sputtering device is equipped with a quadrupole mass spectrometer to monitor the oxygen partial pressure ≤1×10 -3 Pa in real time, and the nitrogen partial pressure is controlled at 0.4 Pa.

[0114] Comparative Example 1. The difference between this comparative example and Examples 1 - 3 is that: there is no gradient functional layer in the process of preparing the cemented carbide composite coating in this comparative example.

[0115] Comparative Example 2. The difference between this comparative example and Examples 1 - 3 is that: in the process of combining the gradient functional layer and the composite layer in the preparation of the cemented carbide composite coating in this comparative example, laser remelting treatment is not carried out.

[0116] Comparative Example 3: The difference between this comparative example and Examples 1 - 3 is that during the preparation of the cemented carbide composite coating in this comparative example, the composite layer is not doped with nano - yttrium trioxide particles.

[0117] Perform performance tests on the cemented carbide composite coatings prepared in Examples 1 - 3 and Comparative Examples 1 - 3. The obtained test data are recorded in the following table:

[0118] Table 1:

[0119]

[0120] Table 2:

[0121]

[0122] Table 3:

[0123]

[0124] By comparing the data in Table 1, it can be seen that compared with the cemented carbide composite coatings prepared by the preparation methods of Comparative Examples 1 - 3, for the cemented carbide composite coatings prepared by the preparation methods of Examples 1 - 3, through the gradient functional layer design with the atomic ratio changing from 1.2:1 in the inner layer to 0.6:1 in the outer layer, a continuous thermal expansion coefficient transition zone is formed within the titanium carbonitride layer. At the same time, from the critical load ≥ 85 N in the data of Examples 1 - 3, it can be known that the interfacial thermal stress is significantly reduced, and at the same time, the interfacial crack density drops significantly. Therefore, the interfacial bonding strength of the cemented carbide composite coating prepared by this method can be significantly improved, which shows that through the gradient design, by alleviating the interlayer thermal mismatch, the delamination resistance of the coating during high - speed cutting can be significantly improved;

[0125] By comparing the data in Table 2, it can be seen that compared with the cemented carbide composite coatings prepared by the preparation methods of Comparative Examples 1 - 3, for the cemented carbide composite coatings prepared by the preparation methods of Examples 1 - 3, after laser remelting treatment during the preparation of the cemented carbide composite coating, an Al - Ti - O eutectic phase is formed at the interface between the gradient functional layer and the composite layer. Combining with the pinning effect of nano - yttrium trioxide on the grain boundaries, the wear rate can be significantly reduced. Without laser remelting treatment, the wear rate increases due to the propagation of interfacial micro - cracks, making up for the technical defect that the commercially available coatings have a high wear rate due to the lack of eutectic strengthening. The synergistic effect of laser remelting and nano - doping significantly improves the wear resistance of the cemented carbide composite coating;

[0126] By comparing the data in Table 3, it can be seen that compared with the cemented carbide composite coatings prepared by the preparation methods of Comparative Examples 1 - 3, for the cemented carbide composite coatings prepared by the preparation methods of Examples 1 - 3, after doping nano - yttrium trioxide particles in the composite layer of the coating, the alumina grain boundaries are pinned, and the oxygen diffusion coefficient can be significantly reduced, and the oxidation increment can reach 2 mg / cm 3The following will illustrate that yttrium sesquioxide significantly extends the lifespan of the coating under the high-temperature condition of 1000 °C through grain boundary pinning and diffusion blocking.

[0127] In the description of this specification, the descriptions referring to terms such as "one embodiment", "example", "specific example", etc. mean that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in a suitable manner in any one or more embodiments or examples.

[0128] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not elaborate on all details and do not limit the invention to the specific embodiments described. Obviously, many modifications and variations can be made according to the content of this specification. These embodiments are selected and specifically described in this specification to better explain the principles and practical applications of the present invention, so that those skilled in the art can well understand and utilize the present invention. The present invention is only limited by the claims and their full scope and equivalents.

Claims

1. A cemented carbide composite coating, characterized in that, It includes the following layer structures deposited in sequence: Substrate layer: A cemented carbide composed of 8 - 10% cobalt by mass, 0.3 - 0.8% chromium carbide, and the balance being tungsten carbide; Intermediate layer: A titanium nitride layer deposited on the surface of the substrate layer by a plasma-enhanced chemical vapor deposition apparatus at 870 - 890 °C and a pressure of 200 MPa; Gradient functional layer: A titanium carbonitride layer with the carbon-nitrogen atomic ratio varying from 1.2:1 in the inner layer to 0.6:1 in the outer layer; Composite layer: An alumina layer, where α-alumina accounts for 50 - 70% by proportion, and the balance is titanium carbonitrogen oxide. The atomic ratio of titanium, carbon, oxygen, and nitrogen in the titanium carbonitrogen oxide is 1:0.6:0.2:0.2; Surface layer: nanocrystalline titanium nitride layer with grain size ≤ 50 nm, deposited using a high-power pulsed magnetron sputtering device under a bias voltage of -100 V to -150 V and a power density of 3-5 W / cm 2 2 2. The cemented carbide composite coating according to claim 1, wherein The thickness of the intermediate layer is 0.2 - 0.5 μm, and the thickness of the gradient functional layer is 4 - 8 μm.

3. The cemented carbide composite coating according to claim 1, wherein The thickness of the composite layer is 1 - 2 μm, and the thickness of the surface layer is 0.5 - 1 μm.

4. The cemented carbide composite coating according to claim 1, characterized in that, The composite layer is doped with nano-yttrium trioxide particles accounting for 0.5 - 1.2% of the total mass of the composite layer. The particle size is 20 - 50 nm and is synchronously injected during the deposition process by an ultrasonic atomization doping apparatus. The atomization frequency is 20 - 40 kHz, and the carrier gas flow rate is 5 - 10 L / min.

5. A method for preparing the cemented carbide composite coating according to any one of claims 1-4, characterized in that, It includes the following steps: Step 1: Substrate pretreatment. The surface of the substrate is treated with a sandblaster, with the abrasive particle size set at 80 - 120 mesh, the compressed air pressure at 0.5 - 0.8 MPa. Then the substrate is transferred to an ultrasonic cleaner and cleaned in a sodium hydroxide solution with a pH value of 10 for 30 min. After that, it is transferred to a radio frequency plasma activation device, with the power set at 300 W, the argon gas flow rate at 50 mL / min, and activated under a vacuum of 1×10 -2 Pa for 20 minutes; Step 2: Depositing the intermediate layer. Using plasma-enhanced chemical vapor deposition, titanium tetrachloride is vaporized and mixed with high-purity nitrogen and hydrogen in a volume ratio of 1:2:4 to form a mixed gas. After the mixed gas enters the deposition chamber, a 10 - 15 MHz radio frequency power supply is applied to generate plasma. The substrate temperature is maintained at 870 - 890 °C, and a - 100 V bias voltage is applied to promote the directional deposition of ions to form a deposited intermediate layer on the substrate surface; Step 3: Depositing the gradient functional layer. Through an MT-CVD apparatus equipped with dual-temperature control, the temperature of the main heating zone is set at 850 - 900 °C, and the temperature of the secondary heating zone is set at 750 - 800 °C. Using an organic nitrogen-carbon compound as the carbon source and nitrogen source, activated carbon and nitrogen groups are generated by decomposition at high temperature. At the same time, a carrier gas is introduced to carry the titanium source compound, and the deposition process is carried out under the condition of 50 - 60 MPa to form a gradient functional layer deposited on the surface of the deposited intermediate layer; Step 4: Depositing the composite layer. Using a multi-source chemical vapor deposition apparatus, the deposition of the composite layer is achieved by alternately controlling two gas paths. The first gas path is a mixed gas of aluminum trichloride, carbon dioxide, and water vapor, and the volume ratio of aluminum trichloride, carbon dioxide, and water vapor is 1:3:0.

05. The second gas path is a mixed gas of titanium tetrachloride and nitrogen, and the volume ratio of titanium tetrachloride and nitrogen is 1:

2. A composite layer is formed on the surface of the gradient functional layer; Step 5: Depositing the surface layer: Using a high-power pulsed magnetron sputtering apparatus, the purity of the titanium target is ≥99.99%, the target-substrate distance is 80 mm, the pulse frequency is 1000 Hz, and the duty cycle is 50%.

6. The preparation method of the cemented carbide composite coating according to claim 1, wherein, It includes the following further processing steps: Step 1: Bonding the substrate layer and the intermediate layer: Under argon protection, the substrate layer and the titanium nitride intermediate layer are placed in a vacuum annealing furnace, heated to 800 - 850 °C at a rate of 15 °C / min, and held for 30 min; Step 2: The transition layer is combined with the functionally gradient layer. Carbon ions with an energy of 40 - 50 keV are implanted into the surface of the transition layer using an ion implantation device, with a beam current density of 60 μA / cm 2 , and a dose of 1×10 17 ions / cm 2 , to form a nanoscale carbon-enriched transition zone; Step 3: The gradient functional layer is combined with the composite layer, and the surface of the gradient functional layer is scanned by a laser remelting device at a wavelength of 1064 nm and a power density of 1×10 4 W / cm 2 under the condition, so that the surface layer area of the gradient functional layer is melted and an Al-Ti-O eutectic phase is formed with the alumina layer; Step 4: The composite layer is combined with the surface layer. Before magnetron sputtering deposition of nano titanium nitride, the surface of the composite layer is bombarded with argon plasma, with a set power density of 0.5 W / cm2 and a time of 10 min to form a rough interface and activate the surface. Then, nano titanium nitride deposition is carried out to fill the interface microstructure with titanium oxide, generating a roughened interface of 5 - 10 nm on the surface of the composite layer, which is the surface layer; Step 5: Overall densification treatment. The coating is placed in a hot isostatic pressing equipment, with a set temperature of 800 - 900 °C and a holding pressure of 1 hour under an argon pressure of 200 MPa, so that the porosity of each layer is ≤ 0.5% and the thickness of the interface diffusion zone is ≥ 0.2 μm.

7. The method for preparing the cemented carbide composite coating according to claim 5, wherein In the sandblasting machine in Step 1, the impeller rotation speed is set at 2600 - 2800 r / min and the abrasive delivery rate is set at 2 - 3 kg / min.

8. The preparation method of the cemented carbide composite coating according to claim 5, wherein, In step 3, the ion implantation equipment is turned on simultaneously to implant nitrogen ions with an implantation energy of 100 keV and a beam current density of 80 μA / cm 2 , and the implantation dose is 3×10 17 ions / cm 2 , and the implantation angle is 15°-30°.

9. The preparation method of the cemented carbide composite coating according to claim 5, characterized in that, In Step 4, interruption is carried out for 5 - 10 min after every 0.5 μm of deposition.

10. The preparation method of the cemented carbide composite coating according to claim 5, characterized in that, In the fifth step, the sputtering chamber of the magnetron sputtering equipment is equipped with a quadrupole mass spectrometer to monitor the oxygen partial pressure in real time ≤ 1×10 -3 Pa, and the nitrogen partial pressure is controlled at 0.3 - 0.5 Pa.

Citation Information

Cited By

  • High-temperature-resistant stainless steel for oven and preparation method thereof

    CN120649017A